Aluminum borate nanowires from the pyrolysis of polyaminoborane precursors. Issue 3 (9th December 2015) - Du, Van An; Jurca, Titel; Whittell, George R.; Manners, Ian
Abstract : Polyaminoboranes [N(R)H-BH2 ] n (1 : R = H, 2 : R = Me) were pyrolyzed on a range of substrates: silicon, metal foils (stainless steel, nickel, and rhodium), and sapphire wafers, as well as on Al2 O3 and AlN powders. Abstract : Polyaminoboranes [N(R)H-BH2 ] n (1 : R = H, 2 : R = Me) were pyrolyzed on a range of substrates: silicon, metal foils (stainless steel, nickel, and rhodium), and sapphire wafers, as well as on Al2 O3 and AlN powders. The pyrolysis of2 on a Si-wafer resulted in porous nanostructures containing hexagonal-boron nitride (h-BN). In the case of1 or H3 N·BH3 as precursor, using rhodium foil as substrate afforded amorphous B and N-containing nanostructures, and polydisperse spherical nanoparticles, respectively. Switching the substrate to sapphire wafers, as well as to Al2 O3 or AlN powders, resulted in formation of crystalline Al5 BO9 nanostructures (nanowires, nanotubes, and nanoribbons). For sapphire wafers, the size of the resulting nanowires was influenced by modifying the surface defect density.